Dual‐band impedance transformer with single shunt stub for complex impedance loads. Issue 7 (15th March 2021) - Liu, Wang; Liu, Qiang; Du, Guangxing; Li, Guolin; Cheng, Dong
Abstract: This letter presents a novel impedance transformer that can transform two unequal frequency‐dependent complex loads (FDCLs) to a resistive load at two diverse bands. The proposed transformer contains four sections of transmission lines and one shunt stub. The design parameters of the transformer are obtained from the analytical formulas. The feasibility analysis of the transformer is discussed and an example based on microstrip technology is implemented and measured for verification. The good agreement between the simulated results and measured results proves the validity of the proposed configuration and design method. Compared with the reported works, the transformer not only features single shunt stub and shorter total electrical length at transmission direction, but also provides simpler analytic design equations and less likely to use the very high‐ or low‐impedance transmission lines.